Polarization and trust in Spanish media during the COVID-19. Identification of audience profiles - Carmen Maria López-Rico; José Luis González-Esteban; Alberto Hernández-Martínez (Universidad Carlos III de Madrid, 2020)
Introduction: During the COVID-19 health crisis, the information in the media has focused mainly on this topic and the interest of citizens has also increased in this regard. Objective: This work shows the profiles of the Spanish users regarding the consumption of information during confinement. Methodology: For this, an online survey was carried out that was pioneering at the time of its launch, which has allowed us to obtain a significant sample. The methodology established for data management has been carried out by counting unique users, machine learning techniques have been used, and the affinity analysis model has been used to discover co-occurrence relationships in the items. Results: In this way, we have been able to determine which means have been most reliable for citizens when it comes to learning about the coronavirus and whether there is a correlation in terms of the means they consume between them. Conclusions: Definitively, co-occurrence has been established between users who trust a certain medium and other means that are also trusted and they have a similar ideological trend.